Dispersion characteristics of liquid jet impacting on the rotating single-layer wire mesh with different surface wettabilities. (6th April 2022) - Liu, Zhi-Hao; Xu, Han-Zhuo; Chen, Wen-Cong; Li, Yan-Bin; Zhang, Liang-Liang; Chu, Guang-Wen
Graphical abstract: Highlights: Effect of surface wettability on dispersion characteristics in RPB was studied. Linear-ligament, curved-ligament, and droplet were observed. Hydrophobic horizontal fiber benefited liquid dispersion in axial direction. Liquid dispersion was intensified by increasing surface hydrophobicity. Abstract: Wire mesh packing is widely used in rotating packed bed reactor to intensify mass transfer of multiphase systems. As an essential parameter of wire mesh, surface wettability was expected to regulate liquid dispersion to influence the mass transfer performance. Hence, the effect of surface wettability on dispersion characteristics of liquid jet impacting on the rotating single-layer wire mesh was investigated via visualization and simulation methods. Three flow patterns, including linear-ligament, curved-ligament, and droplet, were observed. Results indicated that hydrophobic horizontal fiber not only promoted the radial dispersion, but also generated a large axial dispersion angle of liquid. Simulation results revealed that surface wettability influenced the velocity distribution and separation points of the impacting liquid, leading to different dispersion phenomena. Increasing the surface hydrophobicity, liquid initial velocity, and rotational speed could promote the liquid dispersion performance, thereby achieving larger liquid specific surface area ( a s ). Furthermore, correlations to calculate a s were proposed with deviations of ±20%.